CONCEPTUALIZING CONSUMER'S LEARNING ADOPTION OF NEW VALUES - Ignasius Heri Satrya Wangsa Wangsa (Jurnal MEBIS (Manajemen dan Bisnis), 2022)
The era of modernization has produced paradigm shift offering new way of thinking. In the interactive process that links business with its market, new way of thinking has been created within two domains. First, business is conditioned by its competitive environment to adopt product innovativeness. Consequently, new values exist. Second, market has accumulated consumption experience providing references. Within this perspective consumer learning capability is used to respond the existence of new values. This research aims to discuss learning capability where consumer contextualizes new values ie. transforming the values into new context, and at the same time, develops mechanism for values operationalization. Respondents were chosen among undergraduate students of University "X" - Palembang, and Content Analysis of their narratives was applied. Keywords that are related to consumer learning and the adoption of new values were also identified using emergent coding. Then, quantitative approach ie. Regression Analysis was employed to achieve complete understanding of consumer learning in the adoption of new values.